The IBD-disk Is a Reliable Tool to Assess the Daily-life Burden of Patients with Inflammatory Bowel Disease. (27th November 2020) - Tadbiri, Sara; Nachury, Maria; Bouhnik, Yoram; Serrero, Melanie; Hébuterne, Xavier; Roblin, Xavier; Kirchgesner, Julien; Bouguen, Guillaume; Franchimont, Denis; Savoye, Guillaume; Buisson, Anthony; Louis, Edouard; et al.
Abstract: Background and Aim: The inflammatory bowel disease [IBD]-disk is a 10-item self-questionnaire that is used to assess IBD-related disability. The aim of the present study was to evaluate this tool in the assessment of IBD daily-life burden. Methods: A 1-week cross-sectional study was conducted in 42 centres affiliated in France and Belgium. Patients were asked to complete the IBD-disk [best score: 0, worst score: 100] and a visual analogue scale [VAS] of IBD daily-life burden [best score: 0, worst score: 10]. Analyses included internal consistency, correlation analysis, and diagnostic performance assessment. Results: Among the 2011 IBD outpatients who responded to the survey [67.8% of the patients had Crohn's disease], 49.9% were in clinical remission. The IBD-disk completion rate was 73.8%. The final analysis was conducted in this population [ n = 1455 patients]. The mean IBD-disk score and IBD daily-life burden VAS were 39.0 ± 23.2 and 5.2 ± 2.9, respectively. The IBD-disk score was well correlated with the IBD daily-life burden VAS [r = 0.67; p <0.001]. At an optimal IBD-disk cut-off of 40, the area under the receiver operating characteristic curve [AUROC] for high IBD daily-life burden [VAS >5] was 0.81 (95% confidence interval [CI]: 0.79–0.83; p <0.001). Conclusions: In a large cohort of patients, the IBD-disk score was well correlated with IBD daily-life burden, and it could be used in clinical practice.